Hong Kong Security Law 2020: Between State Sovereignty and Breach of Treaty - Ken Bagus Setya Dharma; Aktieva Tri Tjitrawati (Sriwijaya Law Review, 2022)
In 1984 the People's Republic of China (PRC) and the United Kingdom (UK) signed an international agreement to hand over Hong Kong to the PRC on the condition that it be granted a high level of autonomy, except in the field of defence and cooperation with foreign powers. In 2020, PRC Government issued the 2020 Hong Kong Security Law, which contains restrictions on political rights for the people of Hong Kong. This provision will automatically lead to discourse in international law, whether the HKSL 2020 is a manifestation of the implementation of PRC's legal sovereignty or violates the Sino-British Joint Declaration 1984 as a treaty which contains requirements for the transfer of Hong Kong. This article is intended to examine these problems using a normative, historical and conceptual approach. As a result, even though PRC has sovereignty to implement its national law in the territory, the authority must be placed within the limits of compliance with international law. Non-compliance with international treaties will lead to consequences of internationally wrongful acts as a breach of the treaty.